Application of the Monaco-serial biological function for cardiac dose constraints in DIBH-IMRT treatment planning for left-sided breast cancer - Hu, Haili; Jueyi, Zhou; Hao, Jiang; Lai, Jianjun (Frontiers in Oncology, 2025)
BackgroundThe Serial function in the Monaco treatment planning system is essential for cardiac dose optimization in left breast cancer radiotherapy; however its optimal K-value for deep-inspiration breath-hold intensity-modulated radiotherapy (DIBH-IMRT) has not been established. This study aims to determine the evidence-based K-value configuration for clinical implementation.Methods41 left breast cancer patients undergoing DIBH-IMRT were retrospectively analyzed. Plans were stratified by Monaco-Serial K-values: Group A (K=1), B (2≤K ≤ 4), and C (K>4). Dosimetric parameters (heart, LAD, Lung-L) and dose-volume reduction rates (Groups B/C vs A) were compared. Correlations between K-values and DIBH-induced anatomical changes (Lung-L volume increment rate, Lung-L/Heart volume ratio, and Heart-Breast Distance increment) were assessedResultsAll plans satisfied target coverage. Group B achieved optimal cardiac protection: mean heart dose (273.9 ± 91.0 cGy), max heart dose (2676.2 ± 1380.7 cGy), and LAD doses (mean: 411.3 cGy; max: 1483.3 ± 736.3 cGy) significantly decreased versus Group A. Lung-L V500cGy in Group B increased marginally but within clinical tolerance. Correlation analysis confirmed that Group B achieved balanced control of mean/maximum heart doses, aligning with the expected effects of anatomical variations induced by the DIBH technique.ConclusionsAdjusting Monaco-Serial K-value to 2≤K ≤ 4 provides optimal dose constraints for the heart and substructures while ensuring target coverage, making it the optimal parameter setting for left breast cancer DIBH-IMRT.